2016
DOI: 10.3390/ma9120994
|View full text |Cite
|
Sign up to set email alerts
|

Fc-Binding Ligands of Immunoglobulin G: An Overview of High Affinity Proteins and Peptides

Abstract: The rapidly increasing application of antibodies has inspired the development of several novel methods to isolate and target antibodies using smart biomaterials that mimic the binding of Fc-receptors to antibodies. The Fc-binding domain of antibodies is the primary binding site for e.g., effector proteins and secondary antibodies, whereas antigens bind to the Fab region. Protein A, G, and L, surface proteins expressed by pathogenic bacteria, are well known to bind immunoglobulin and have been widely exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 75 publications
(92 reference statements)
2
118
1
1
Order By: Relevance
“…Additionally, their small sizes allow for reduction of the linkage error to the true target position as shown with EGF receptor and microtubule imaging. In the future, these small secondary binders can be evaluated for more species and IgG subclasses, as well as engineered for higher affinity . In addition, engineering of these proteins to carry unique chemical groups such as cysteine or unnatural amino acid residues could be employed for quantitative 1:1 labeling of protein to docking strands, which would enable applications in the direction of quantitative imaging such as quantitative points accumulation in nanoscale topography (qPAINT) …”
Section: Figurementioning
confidence: 99%
“…Additionally, their small sizes allow for reduction of the linkage error to the true target position as shown with EGF receptor and microtubule imaging. In the future, these small secondary binders can be evaluated for more species and IgG subclasses, as well as engineered for higher affinity . In addition, engineering of these proteins to carry unique chemical groups such as cysteine or unnatural amino acid residues could be employed for quantitative 1:1 labeling of protein to docking strands, which would enable applications in the direction of quantitative imaging such as quantitative points accumulation in nanoscale topography (qPAINT) …”
Section: Figurementioning
confidence: 99%
“…Therefore,i ti si mportant to investigate how these potential problems can be circumvented through sitespecific conjugation. [11] In this context, we decided to focus on monoclonal antibodies,e specially in ADCs and to extend the cleavable linker technology [12] established for protein modification by using an Fc affinity peptide [13] instead of as mall molecule.O ur affinity peptide labelling of immunoglobulin G( IgG), which we reported previously, [14] has the potential to facilitate the specific conjugation of amultitude of native lysine residues.Herein, we report anew technology that achieves the regiodivergent functionalization of three lysine residues in the mAbs by simply changing ap eptide sequence,t ermed AJICAP.W eh ave demonstrated that ADCs generated by this novel regiodivergent conjugation technology can show retained antigen recognition and in vivo anti-tumor activity in xenograft mouse studies. Moreover,i n2 017, Ohata and Ball [9] reported af unctionalization method using ah exa-rhodium metallopeptide catalyst to modify as pecific asparagine in the Fc C H2 domain of an on-mutated antibody, but this method still presents difficulties in controlling the conjugation site and number of payloads.…”
mentioning
confidence: 99%
“…[13] Protein Ai saversatile protein framework that binds to the Fc region. [13] Protein Ai saversatile protein framework that binds to the Fc region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BP180 depletion was observed under stimulation with BP180 C-term-IgG in the presence of anti-Fc/protein G. This suggests that BP180 C-term-IgG gains pathogenicity under certain conditions. To confirm the pathogenicity in vivo, we tested the skin fragility of mice injected with mAbs against BP180 and anti-Fc (1,2) were used as substrates for western blotting. Blotting was performed by HRP-conjugated anti-human IgG Fc, anti-mouse IgG Fc or anti-rabbit IgG Fc without a primary antibody.…”
Section: Discussionmentioning
confidence: 99%